Correlation of the in vitro biotransformation of H3B-6527 in dog and human hepatocytes with the in vivo metabolic profile of 14C-H3B-6527 in a dog mass balance study. (2nd April 2020) - Colombo, F.; Smith, S.; Lai, G. W.; Nix, D.; Smith, P. G.; Schindler, J.; Rioux, N.
Abstract: 1. H3B-6527 is an orally available covalent small molecule inhibitor of FGFR4 undergoing evaluation in adults with hepatocellular carcinoma. Absorption, metabolism, transport and elimination of H3B-6527 were investigated in vitro and in a 14 C-H3B-6527 beagle dog mass balance study. 2. Following intravenous dosing in dogs, unchanged 14 C-H3B-6527 represents only 1.6% of the total dose in excreta. The low amount of radioactivity in the dog urine (4.9% of the administered dose), suggests that renal elimination is a minor pathway of clearance for H3B-6527. A majority of the radioactivity was observed in the feces up to 5 days after dose administration, suggesting that drug-related material was secreted in the bile, and that H3B-6527 clearance was mostly driven by metabolism. 3. In vitro, H3B-6527 is a substrate of GSTs, CYP3A and P-glycoprotein. 4. The major pathways of metabolism were similar in human and dog hepatocytes, and occurred via glutathione (GSH) conjugations and sequential hydrolysis, N -deethylation and hydroxylation. 5. The metabolic profile of H3B-6527 was qualitatively similar in dog hepatocytes and plasma/excreta. Trial registration: ClinicalTrials.gov identifier: NCT02834780.